To find the solution for the system of equations using Jian's table, we can look for the pair of x- and y-values where the outputs from both equations are the same.
From the table we have:
For the equation \(y = 2x - 5\):
- At \(x = 0\), \(y = -5\)
- At \(x = 1\), \(y = -3\)
- At \(x = 2\), \(y = -1\)
- At \(x = 3\), \(y = 1\)
For the equation \(y = x - 3\):
- At \(x = 0\), \(y = -3\)
- At \(x = 1\), \(y = -2\)
- At \(x = 2\), \(y = -1\)
- At \(x = 3\), \(y = 0\)
Now, let's look for the x-value where the y-values from both equations are equal:
-
At \(x = 0\):
- \(y = 2(0) - 5 = -5\)
- \(y = 0 - 3 = -3\)
-
At \(x = 1\):
- \(y = 2(1) - 5 = -3\)
- \(y = 1 - 3 = -2\)
-
At \(x = 2\):
- \(y = 2(2) - 5 = -1\)
- \(y = 2 - 3 = -1\) (same value)
-
At \(x = 3\):
- \(y = 2(3) - 5 = 1\)
- \(y = 3 - 3 = 0\)
The only point where the y-values from both equations are equal is \( (2, -1) \).
Thus, the solution to the system of equations is:
(2, −1).